THE EFFECT OF PROFITABILITY, LIQUIDITY, FIRM SIZE AND ASSET STRUCTURE ON CAPITAL STRUCTURE - Yulianti, Melly Maragretha; Friyani, Rita; Tiswiyanti, Wiwik (Faculty of Economics and Business Universitas Jambi, 2026)
Capital structure is a critical financial decision, particularly for mining companies characterized by high capital requirements and high business risk. Inconsistent findings in prior studies regarding the determinants of capital structure highlight the need for further research. This study examines the effects of profitability, liquidity, firm size, and asset structure on the capital structure of mining companies listed on Indonesia Stock Exchange during 2019-2023. The sample was selected using purposive sampling based on criteria including mining companies listed, publishing annual financial statements, and reporting profits. Based on these criteria, 25 companies were selected with an observation period of five years, resulting in a total of 125 observations. The analytical methods applied include multiple linear regression and descriptive analysis, using SPSS version 27, the primary statistical tool. The results indicate that profitability, liquidity, and asset structure have a significant negative effect on capital structure, while firm size does not. This study finds that the financing decisions of mining companies are broadly consistent with the pecking order theory, particularly with respect to profitability and liquidity. The negative effect of asset structure reflects the capital-intensive and high-risk characteristics of the mining industry, especially during 2019-2023, which includes the COVID-19 pandemic and heightened global economic volatility, leading firms to adopt more cautious debt policies. In addition, these findings contribute to practical guidance for management in determining optimal financing policies and assists investors in evaluating risks and investment decisions.